Organization and evolution of naphthalene catabolic pathways: sequence of the DNA encoding 2-hydroxychromene-2-carboxylate isomerase and trans-o-hydroxybenzylidenepyruvate hydratase-aldolase from the NAH7 plasmid. - Eaton, R W (1994)
The sequence of a 2,437-bp DNA segment from the naphthalene upper catabolic pathway operon of plasmid NAH7 was determined. This segment contains three large open reading frames designated nahQ', nahE, and nahD. The first of these is the 3' end of an open reading frame that has no known function, the second (993 bp) encodes trans-o-hydroxybenzylidenepyruvate hydratase-aldolase (deduced molecular weight, 36,640), and the third (609 bp) encodes 2-hydroxychromene-2-carboxylate isomerase (deduced molecular weight, 23,031). This DNA has a high degree of sequence homology (greater than 91% for the first 2161 bp) with a DNA segment from the dox (dibenzothiophene oxidation) operon of Pseudomonas sp. strain C18, which encodes a pathway analogous to that encoded by NAH7. However, 84 bp downstream from nahD, the last gene in the nah operon, this homology ends. This 84-bp sequence at the downstream end of nah and dox homology has 76% homology to a sequence that occurs just upstream of the nah promoter in NAH7. These directly repeated 84-bp sequences thus encompass the upper-pathway nah operon and constitute the ends of a highly conserved region.